WIRELESS-BASED EDUCATION INFORMATION SYSTEM IN MATARAM: DESIGN AND IMPLEMENTATION - Muhammad Tajuddin; Zainal A Hasibuan; Abdul Manan; Nenet Natasudian Jaya (Universitas Raharja, 2012)
Education requires Information Technology (IT) for facilitating data processing, fastening data collecting, and providing solution on publication. It is to reach the Education National Standard which needs a research. The survey will use questionnaires as data collector for explanatory or confirmatory in constructing the System Development Life Cycle (SDLC) using structured and prototyping techniques, so a planning is by anticipating the changes. It comprises 5 subsystems; Human Resources, Infrastructures & Equipment, Library, GIS Base School Mapping, and Incoming Students Enrollment. The construction is aimed to ease information access connected among schools, Education Service, and society, integrating and completing each other.